Using smart contracts to enhance an industrial symbiosis process - Gon?alves, Ricardo Miguel Silva (2022)
Industrial Symbiosis is a subfield of Circular Economy that tries to solve the issue of the enormous amount of Industrial waste. The main objective of this field is to create networks of companiies where a by-product/waste of one is of the principal resources of another one. To run these types of Industrial Symbiosis networks, companies require the creation and maintenance of trusted and transparent relationships between all enntities. These relationships are a constant challenge to maintain. When a new entity wants to join the network, it requires trust in each current member. In an Industrial Symbiosis context, a blockchain-based system can reduce the work necessary to establish and maintain these networks. The system can serve as a ground truth between all the entities operating at a national mor global scale, removing all the overhead of establishing and maintaining relationships between all parties. This thesis proposes a scalable and modular blockchain architecture design using smart contracts to enhance the industrial symbiosis process of the Pulp, Paper, and Cardboard Production Sector companies in portugal. The system will implement all the requirements using smart contracts. The design comprehends all entities participating in the requiremennts using smart contracts. the design comprehends all entities participating in the network, namely the Pulp and Paper companies, the Sand Producers, the Mortar Producers, the organization that uses the resulting material mixture, and the Environmental Portuguese Agency (EPA) [13]. The base blockchain technology used to implement the architecture is Hyperledger Fabric, by being a permissioned ledger, prevents unwanted accesses to the network. Fabric also provides the required trust and transparency between all entities.